Fish Bio-Diversity and Livelihood of Fishers of Dekar Haor in Sunamganj of Bangladesh (Journal of the Asiatic Society of Bangladesh, Science, 2017)
The study was carried out to assess the present status of fish biodiversity in Dekar haor and livelihood of fishermen living around the haor under Sunamganj district during 12 months from September 2015 to August 2016. Monthly fish samples were collected from the catches of fishermen and identified based on meristic and morphometric characteristics. A total of 51 fish species belonging to 34 genera along with two prawn species under 19 families was found. Among them catfishes were most abundant. The values of Shannon-Weiner diversity (H′), Margalef’s richness (d), Pielou’s evenness indices (J′) and Simpson dominance indices (c) ranged from 3.36-3.78, 6.12-8.40, 0.98- 0.99 and 0.97-0.98, respectively. Livelihood data were collected through direct interview from randomly selected 73 fishermen. Main occupation of fishermen is fishing. There were three age groups such as young (18-35 years), middle (36-45 years) and old group (above 46 years) where young group was mostly involved in fishing. Most of the fishermen (72.61%) were Muslims and 63% were able to sign only followed by others. Annual income of fishermen varied from Tk. 10,000-100,000. Majority of them had low savings with poor housing and sanitation facilities. Maximum fishers are interested to live in unit family owing to low income. Results of this study imply that fish diversity status was not satisfactory. Also livelihood condition of fishers was not so good. Therefore, appropriate measures should be taken to improve the livelihood of fishermen and to protect the bio-diversity of the haor.Asiat. Soc. Bangladesh, Sci. 43(2): 233-244, December 2017